2015
DOI: 10.1089/mdr.2015.0033
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Flies in Disseminating Plasmids with Antimicrobial-Resistance Genes Between Farms

Abstract: Dissemination of antimicrobial resistance is a major global public health concern. To clarify the role of flies in disseminating antimicrobial resistance between farms, we isolated and characterized tetracycline-resistant Escherichia coli strains isolated from flies and feces of livestock from four locations housing swine (abattoir, three farms) and three cattle farms. The percentages of isolates from flies resistant to tetracycline, dihydrostreptomycin, ampicillin, and chloramphenicol (80.8%, 61.5%, 53.8%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
1
31
0
2
Order By: Relevance
“…Previous studies have discussed the role of flies as vectors of antimicrobial resistance bacteria (Blaak et al, 2014;Davari et al, 2010;Literak et al, 2009;Liu et al, 2013;Macovei and Zurek, 2006;Marshall et al, 1990;Rahuma et al, 2005;Rybaříková et al, 2010;Schaumburg et al, 2016;Solà-Ginés et al, 2015;Usui et al, 2015Usui et al, , 2013Von Salviati et al, 2015;Wang, 2013;Wang et al, 2017;Zurek and Ghosh, 2014). In Brazil, Almeida et al (2014) isolated E. coli, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have discussed the role of flies as vectors of antimicrobial resistance bacteria (Blaak et al, 2014;Davari et al, 2010;Literak et al, 2009;Liu et al, 2013;Macovei and Zurek, 2006;Marshall et al, 1990;Rahuma et al, 2005;Rybaříková et al, 2010;Schaumburg et al, 2016;Solà-Ginés et al, 2015;Usui et al, 2015Usui et al, , 2013Von Salviati et al, 2015;Wang, 2013;Wang et al, 2017;Zurek and Ghosh, 2014). In Brazil, Almeida et al (2014) isolated E. coli, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…After detecting E. coli clones from flies and calf feces with the same antimicrobial resistance profile, Usui et al (2015Usui et al ( , 2013 suggested that flies can disseminate antimicrobial resistance genes not only within farm but also between farms. Similarly, Solà-Ginés et al (2015) found the same Extended-spectrum β-lactamase (ESBL)-producing E. coli clone isolated from flies within two broiler farms and suggested it may have happened because flies can travel long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a large amount of flies were present at Farm 4. Flies are known to transmit bacteria including E. coli [94, 95]. …”
Section: Discussionmentioning
confidence: 99%
“…On-farm transmission of AMR has been characterized in the literature for a wide range of animals: pigs (Crombé et al, 2013; Novais et al, 2013), cows (Wichmann et al, 2014), and insects (Zurek and Ghosh, 2014; Usui et al, 2015; Hammer et al, 2016). A recent review of the academic literature that address the issue of antibiotic use in agriculture suggests that only seven studies (five percent) argued that there was no link between antibiotic consumption in animals and resistance in humans, while 100 (72%) found evidence of a link (O’Neill and The Review on Antimicrobial Resistance, 2015).…”
Section: Drivers Of Resistance: Antibioticsmentioning
confidence: 99%